2013
DOI: 10.1002/ana.23788
|View full text |Cite
|
Sign up to set email alerts
|

Digestion products of the PH20 hyaluronidase inhibit remyelination

Abstract: OBJECTIVE Oligodendrocyte progenitor cells (OPCs) recruited to demyelinating lesions often fail to mature into oligodendrocytes (OLs) that remyelinate spared axons. The glycosaminoglycan hyaluronan (HA) accumulates in demyelinating lesions and has been implicated in the failure of OPC maturation and remyelination. We tested the hypothesis that OPCs in demyelinating lesions express a specific hyaluronidase, and that digestion products of this enzyme inhibit OPC maturation. METHODS Mouse OPCs grown in vitro we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
127
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 98 publications
(134 citation statements)
references
References 59 publications
4
127
3
Order By: Relevance
“…This finding is in contrast to work in our laboratory showing that OPCs digest hyaluronan (HA), and that PH20, but not other hyaluronidases, as well as PH20‐generated digestion products of HA potently block OPC maturation and remyelination 2. The basis for the claim that PH20 does not influence OPC maturation is that in the Marella et al paper, the authors report that the effects of a preparation of hyaluronidase, bovine testicular hyaluronidase (whose hyaluronidase activity is mostly PH20), are due entirely to contaminating fibroblast growth factor‐2 (FGF‐2; also called basic fibroblast growth factor).…”
contrasting
confidence: 95%
See 3 more Smart Citations
“…This finding is in contrast to work in our laboratory showing that OPCs digest hyaluronan (HA), and that PH20, but not other hyaluronidases, as well as PH20‐generated digestion products of HA potently block OPC maturation and remyelination 2. The basis for the claim that PH20 does not influence OPC maturation is that in the Marella et al paper, the authors report that the effects of a preparation of hyaluronidase, bovine testicular hyaluronidase (whose hyaluronidase activity is mostly PH20), are due entirely to contaminating fibroblast growth factor‐2 (FGF‐2; also called basic fibroblast growth factor).…”
contrasting
confidence: 95%
“…We also reported, using size exclusion chromatography with multi‐angle laser light scattering, that distinct hyaluronidases generated HA digestion products that varied in their size ranges 2. We found that PH20‐digested HA but not HA digested by another hyaluronidase blocked OPC maturation.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…A recent report suggested that HA fragments generated by PH20 in vitro inhibited differentiation of oligodendrocyte progenitor cells (OPC) and subsequent remyelination of brain lesions in a mouse model [17]. However, the key experiments characterizing the effect of HA fragments in this remyelination model used BTH-digested HA rather than rHuPH20-digested HA or purified LMW HA fragments, again raising the possibility that the observed effect might have been influenced by reagent contamination.…”
Section: Mifmentioning
confidence: 99%